Demographic Impact of the Black Swan Events - Hajdúková, Jana; Langhamrová, Jitka, 1958-; Miskolczi, Martina; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2014)
Demographic development of the population is not considered as a regular one, although there are some patterns when describing it. Black Swan is the metaphorical name introduced in 2007 by N. N. Taleb in his book of the same name. This term and corresponding theory was constructed for the specific type of events that seem to be random and that have surprisingly large effect, major impact, although in hindsight these events seem inevitable and possible to rationalize. During the history of mankind, there have been many events that can be classified as Black Swans. These events influenced the field of science, technology, business or culture. Are there Black Swan events that significantly influenced the demographic development of the population? This thesis aims to describe in detail four events occurring during the last century and study whether the impact of those events on the demographic behaviour of the population was significant or not. Retrospectively, the events are terrorist attacks from 11th September 2001, dissolution of the Soviet Union at the turn of the years 1991 and 1992, Soviet occupation in former Czechoslovakia in August 1968 and the World War I. The First World War and the dissolution of the Soviet Union are exactly the events that seem to have noticeable reflection in the demographic development of the populations concerned. Although the Black Swan events are significant for the population due to the influence and its depth, it cannot be claimed that the same statement is valid for the demographic impact itself. Presented thesis illustrates on the chosen examples that demography does not have to be directly influenced by the events denoted as Black Swan.
Vedoucí práce: Jitka Langhamrová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická demografie [obor dipl. práce]; diplomové práce; master's theses